2018
DOI: 10.1051/e3sconf/20184500060
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of air pollutant concentrations and inflow trajectories: a case study of selected cities in South-Eastern Poland

Abstract: Abstract. The paper presents a comparison of air pollutant concentrations in three cities in South-Eastern Poland (Krakow, Tarnow and Rzeszow) using statistical analyses and backward trajectory modelling (the HYSPLIT model). The analyses were based on particulate matter (PM10), nitrogen dioxide (NO2) and sulphur dioxide (SO2) levels as well as meteorological data from year 2017. The performed analyses revealed, among others, that the PM10 and SO2 concentrations in the air depend on the season of the year, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…On this basis, it can be concluded that this type of stations differs most from the others in terms of NO 2 concentration, which, among the pollutants analyzed in the study, seems to be the most typical pollution for road transport. No significant differences between the winter and summer months or the transition period for NO 2 concentrations in the air at traffic stations is confirmed by the results obtained in previous studies [22,61,75]. Strong seasonal variations of the air concentrations observed for the rest of analyzed substances can be explained, on the one hand, by higher emissions (municipal and household sector), and on the other hand, it results from weaker ventilation and a lower mixing-layer height, which was already demonstrated for previous years, e.g., in the works [58,60,64].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On this basis, it can be concluded that this type of stations differs most from the others in terms of NO 2 concentration, which, among the pollutants analyzed in the study, seems to be the most typical pollution for road transport. No significant differences between the winter and summer months or the transition period for NO 2 concentrations in the air at traffic stations is confirmed by the results obtained in previous studies [22,61,75]. Strong seasonal variations of the air concentrations observed for the rest of analyzed substances can be explained, on the one hand, by higher emissions (municipal and household sector), and on the other hand, it results from weaker ventilation and a lower mixing-layer height, which was already demonstrated for previous years, e.g., in the works [58,60,64].…”
Section: Discussionsupporting
confidence: 86%
“…Poor air quality in Krakow, often observed during the heating season, is usually associated with unfavorable synoptic-scale (anti-cyclonic circulation), low temperature, low mixing-layer height and low wind speed, which hinders the dispersion of pollutants in the air [58,60,61,64,65], and in the case of fine solid particles with increased formation of secondary inorganic (SIA) or organic (SOA) aerosols [62,[68][69][70][71] and a large inflow background of dust pollution from adjacent areas [22,24,65,67]. Despite a significant reduction of SIA precursor emissions from large combustion plants (SO 2 and NO x ) and residential heating (SO 2 ), the contribution of SIA formation in fine particulate matter is now much greater [68][69][70] than it has been reported for several years ago [72,73]; this indicates an increase in the role of NO x (derived from combustion processes, including to a large extent from the combustion of engine fuels) in the formation of SIA, and thus their greater impact on the levels of fine particulate matter in the air [91,92,97].…”
Section: Discussionmentioning
confidence: 99%
“…There has not been much discussion of the importance of numerous garbage burnings as a local or global cause of air pollution [36]. Due to the intense heat present during a fire, the smoke that is released is usually immediately elevated and spreads much above ground level [37]. Sulphur dioxide (SO 2 ) and nitrogen dioxide (NO 2 ) from waste burning cause acid rain.…”
Section: Air Pollutionmentioning
confidence: 99%
“…For example, the nearest state meteorological station belonging to the Institute of Meteorology and Water Management (IMGW) was located approximately 10-18 km from the individual canyons, on the outskirts of the city, near Krakow Airport (Figure 1). However, data from this station were not used in this study due to the fact that it was located in an open area and was characterized by much higher average wind speeds and a different wind rose compared to the station located at AGH University [80]. Total solar radiation included in the OSPM model in modeling the course of photochemical reactions involving nitrogen oxides was captured from the ERA5 meteorological reanalysis provided by the European Center for Medium-Range Weather Forecasts (ECMWF) [81].…”
Section: Meteorological Data and Background Of Air Pollutantsmentioning
confidence: 99%